Smart grid communication concept for frequency control in distribution system - Jamian, J.J.; Mustafa, M.W.; Mokhlis, Hazlie; Baharudin, M.A. (IEEE, 2011)
The advancement of electrical device technologies can be used to balance the frequency of the system by adjusting their power consumption. However, this can only be achieved by having good data communication management. The introduction of Smart Home System (which consists of Smart Appliance (SA) and Smart Meter (SM)), Smart Regional Server (SRS) and Smart Server (SS) will be used to manage data communication in smart distribution system. The communications between these devices will be via Power Line Communication (PLC), and WiMAX will be used as a medium to transfer the data to the SRS. Transport Control Protocol (TCP) will increase the reliability of transferring data. By having good communication and architecture, as well as good management and decision making by the servers and smart metering, the use of load-balancing control to maintain the frequency of the system within the acceptable limit in smart distribution grid system will be achieved.